Monitoring the Sequential Organ Failure Assessment score in nonocclusive mesenteric ischemia increases the survival rate: A single-center observational study. Issue 48 (3rd December 2021) - Murata, Takaaki; Kawachi, Jun; Igarashi, Yuto; Suno, Yuma; Nishida, Tomoki; Miyake, Katsunori; Isogai, Naoko; Fukai, Ryuta; Kashiwagi, Hiroyuki; Shimoyama, Rai; Hirata, Masahiro; Shinozaki, Nobuaki
Abstract : Abstract: Several large-scale studies have assessed the endovascular and surgical treatments for nonocclusive mesenteric ischemia (NOMI); nonetheless, the prognostic factors for NOMI remain unclear. In this single-center study, we retrospectively reviewed the electronic medical records of 197, 149 patients were retrieved from the inpatient database of our hospital from January 2011 to January 2020; 79 patients with NOMI were observed. A total of 44 patients who underwent laparotomy were statistically analyzed and divided into the survivor and non-survivor groups. Prognostic factors were compared between the 2 groups. Exploratory laparotomy based on a second-look surgery was the first treatment choice. The overall mortality rate was 61.3%, with a male-to-female ratio of 1.6:1. The median Sequential Organ Failure Assessment (SOFA) score was 11.06 [5.75-17.25]. The median SOFA score was 5 [interquartile range: 3-8] in the survivor group and 14.8 [interquartile range: 10.5-19] in the non-survivor group. The log-rank test showed a significant difference in the presence of diabetes mellitus ( P = .025), hypoglycemia ( P = .001), SOFA score ≥10 ( P  < .001), hemoglobin levels ≥11 g/dL ( P  = .003), platelet count ≥12.9 × 10 4 /μL ( P  = .01), lactate levels ≥2.6 mmol/L ( P  = .005), and base excess <-3.0 ( P < .023). Multivariate analysis using the factors with significant differences revealed that SOFA score ≥10 (hazard ratio for death, 1.199; 95% confidence interval, 1.101-1.305; P  < .001) was an independent prognostic factor. The SOFA score can be used to assess disease severity. A SOFA score of ≥10 may be associated with increased mortality.